A Greek physician's portrait in Windsor Castle. (August 2019) - Bartsocas, Christos S
To the visitor to Windsor Castle, the Thomas Lawrence portraits in the Waterloo Chamber represent the most important contributors to the military defeat of Napoleon Bonaparte, by British, Prussian, Russian and Austrian forces at the Battle of Waterloo. Nevertheless, only few individuals realise that a Greek physician, Count Ioannis Capodistrias, a native of the island of Corfu, stands among these leading personalities as a diplomat, the Russian Minister of Foreign Affairs, who contributed remarkably to European unity in the early nineteenth century and as a statesman ('Governor' of Greece) with a tragic end to his life, after establishing a Greek State practically from ruins.